BIAYA DAN PENDAPATAN USAHATANI TEBU MENURUT STATUS KONTRAK (Studi Kasus di PT IGN Cepiring, Kab. Kendal) - Dita Yuniar Saskia; Waridin Waridin (Universitas Diponegoro, 2012)
ABSTRACT Indonesian land are potentially to be planted with sugarcane, especially in Java Island. It had proven that in 1928 three-fourth of total export in Java comes from sugar industry. Today, Java Island still potential to plant with sugarcane. It can be see that land of sugarcane is tend to increase till 277.630 ha in 2010. PT IGN Cepiring in Kendal District is a sugar mill that re-operate to reach “Swasembada Gula” program in Central Java. PT IGN Cepiring can receive sugarcane till 1.800 ton each day. PT IGN Cepiring interlaces relationship with sugarcane farmers around. The relationship is implemented in credit contract and mill contract. This research has purpose to describe costs, revenue, and returns of sugarcane farmer based on contract status at PT IGN Cepiring. Then, to analise are there any significant different between return of credit contract’s farmer and mill contract’s farner. Data that used is primary data which collected by interview with sugarcane farmer who has relationship with PT IGN Cepiring. The result shows that credit contract’s farmer has less total cost, and more revenue that mill contract’s farmer. Based on result of t-test that return of credit contract’s farmer has significant different with mill contract’s farmer (P-value 0,000 < 0,05).